Landasan Filosofis, Psikologis, dan Sosiologis dalam Dasar-Dasar Kependidikan - Diva Febriani Safitri; Amelia Putri; Gusmaneli (Jurnal Pendidikan Sosial Dan Konseling, 2024)
This research discusses the philosophical, psychological and sociological foundations of education in Indonesia. The philosophical foundation emphasizes the importance of applying Pancasila values to shape student character. Psychological foundations highlight understanding of students' developmental stages and creating an inclusive learning environment. Meanwhile, the sociological basis sees education as an important tool for social mobility and reducing social inequality. This research uses a qualitative approach with literature study and education policy analysis. The research results show that the application of this educational foundation is very important to produce a generation that is not only academically intelligent, but also has noble character.